2008
DOI: 10.1200/jco.2007.15.4278
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Intravascular Large B-Cell Lymphoma Treated With Rituximab-Containing Chemotherapy As Reported by the IVL Study Group in Japan

Abstract: Our data suggest improved clinical outcomes for patients with IVLBCL in the rituximab era. Future prospective studies of rituximab-containing chemotherapies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
217
3
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(238 citation statements)
references
References 31 publications
(1 reference statement)
9
217
3
7
Order By: Relevance
“…Treatment outcomes have significantly improved with the addition of rituximab to standard anthracycline based chemotherapy. Shimada et al [12] compared treatment outcomes for IVLBCL in Asian patients using chemotherapy with and without rituximab and noted a significantly higher complete response rate (82% rituximab group versus 51% nonrituximab group) and progression-free/overall survival at 2 years (56%/66% rituximab group; 27%/46% nonrituximab group). Similar results were achieved in a report from Ferreri et al [19] using immunochemotherapy in Western patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment outcomes have significantly improved with the addition of rituximab to standard anthracycline based chemotherapy. Shimada et al [12] compared treatment outcomes for IVLBCL in Asian patients using chemotherapy with and without rituximab and noted a significantly higher complete response rate (82% rituximab group versus 51% nonrituximab group) and progression-free/overall survival at 2 years (56%/66% rituximab group; 27%/46% nonrituximab group). Similar results were achieved in a report from Ferreri et al [19] using immunochemotherapy in Western patients.…”
Section: Discussionmentioning
confidence: 99%
“…IVLBCL is usually treated with anthracycline-containing regimen. Since the lymphoma cells are CD201, rituximab had to be a part of the treatment regimen [12]. Serology for infectious hepatitis had to be obtained prior to therapy with rituximab.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study suggested a survival benefit with the addition of R to chemotherapy for IVLBCL; the 2-year OS for 49 patients treated with R-chemotherapy was significantly higher than that of 57 patients treated with chemotherapy alone (66% vs. 46%; p = 0.02). 48 In IVLBCL patients without CNS involvement at initial diagnosis, the risk of CNS recurrence at 3 years was 25% with a median follow-up in survivors of 39 mon. 49 At present, a phase II trial of R-CHOP combined with high-dose-methotrexate (HD-MTX) and intrathecal administration of MTX to prevent CNS relapse for untreated IVLBCL is ongoing in Japan (UMIN000005707).…”
Section: Intravascular Large B-cell Lymphomamentioning
confidence: 99%
“…Among the patients with IVLBCL, the 2-year survival and progression-free survival rates in the rituximab group were 66% and 56%, compared to the group without rituximab, 46% and 27% respectively. 22 IVLBCL is a very rare cause of nephrotic syndrome and acute kidney injury. FDG-PET-CT may be especially very helpful for the early diagnosis of IVLBCL.…”
Section: Case Presentationmentioning
confidence: 99%